A study on the effects of language and visual art integrated teaching on language learning performance and satisfaction of ethnic minority students in China - Zhang, Yao; Jia, Simeng (Frontiers in Psychology, 2022)
Innovative technological products are present in students' environments. Information explosion and popularity are affecting their thoughts, and there is a large amount of information fuel in life through the Internet, television, movies, and advertisements. This phenomenon transforms reading from pure words into image. The current study was conducted using an experimental design model. A total of 188 ethnic minority students in the Hebei Province participated in the experimental study. The experimental group went through language and visual art integrated instruction, while the control group underwent traditional teaching. The experimental study lasted for 20 weeks (3 h per week). The research results showed that (1) spoken and written artistic conception was displayed through artistic expression. Ethnic minority students' differences in language skills and artistic expression were found to be the major factors that were effective in the production process. These aspects made the work richer and even more diversified. (2) After joining the classes and covering several lessons, ethnic minority students were found to be getting increasingly better in terms of integrating art vocabulary into their conversation. (3) Language and visual art integrated teaching input was a story content, which was received through “listening”, while the outputs were individual opinions through “speaking”. Their thoughts were presented through “painting”. The creation process operated in the brain and reflected differences in terms of their thinking skills, vocabulary organizational skills, language use, and creativity. Based on the results, this study is expected to improve the language proficiency of ethnic minority students, enhance their artistic culture, and pave the way for their understanding and attitude toward language and literature.